2018
DOI: 10.1371/journal.pgen.1007608
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene-diet pair modulates C. elegans aging

Abstract: Diet profoundly affects metabolism and incidences of age-related diseases. Animals adapt their physiology to different food-types, modulating complex life-history traits like aging. The molecular mechanisms linking adaptive capacity to diet with aging are less known. We identify FLR-4 kinase as a novel modulator of aging in C. elegans, depending on bacterial diet. FLR-4 functions to prevent differential activation of the p38MAPK pathway in response to diverse food-types, thereby maintaining normal life span. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 59 publications
0
52
0
2
Order By: Relevance
“…The gene encoding for the Toll/interleukin-1 receptor adaptor protein TIR-1, an essential component of the innate immune response in nematodes (Liberati et al 2004), was found to be significantly upregulated in both hsb-1(-) and hsf-1 overexpression strains (Tables S1 and S2). Interestingly, a recent study has shown a major role of tir-1 in mediating the life span extension associated with activation of p38 MAPK pathway in C. elegans (Verma et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The gene encoding for the Toll/interleukin-1 receptor adaptor protein TIR-1, an essential component of the innate immune response in nematodes (Liberati et al 2004), was found to be significantly upregulated in both hsb-1(-) and hsf-1 overexpression strains (Tables S1 and S2). Interestingly, a recent study has shown a major role of tir-1 in mediating the life span extension associated with activation of p38 MAPK pathway in C. elegans (Verma et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The p38-MAPK pathway mutants were susceptible to oxidative stress 14 . The increased life span of daf-2 mutants 15 and the food-type dependent life span of flr-4 mutant are dependent on p38-MAPK pathway components 70 . In most of the cases, the activation of the p38-MAPK pathway correlates with the phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…The C. elegans p38-MAPK pathway is involved in diverse aspects of cellular function, including development 65,66 , stress response 14,18 , innate immunity 15,25,67,68 , metabolism, and longevity 69,70 . In all these cases, when a component of the p38-MAPK pathway was mutated, the phenotype was adversely affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the effects on lifespan, when manipulating orthologous lifespan-associated genes in different model organisms, are mostly concordant, despite high evolutionary distances between them [ 15 ]. Most recently, C. elegans has come to enjoy increasing popularity as a model for health [ 16 , 17 ], and an ever increasing number of compounds [ 18 21 ] and diets [ 22 , 23 ] are tested in C. elegans for their anti-ageing and health effects.…”
Section: Introductionmentioning
confidence: 99%